Verstehen verstehen Eine erkenntnistheoretische Untersuchung - Malfatti, Federica Isabella (Schwabe Verlag, 2022)
This book explores the nature and normativity of the epistemic state of understanding. Particular attention is devoted to the relation between understanding and truth, the relation between understanding and explanation, and the relation between understanding and knowledge. The author defends the claim that understanding is a (moderately) factive epistemic state not necessarily achieved with the aid of explanations and probably different than knowledge.